War and governance international security in a changing world order - Weitz, Richard (Changing face of war., 2011)
How do we avoid war? To arrive at an answer, master analyst Richard Weitz explores the ways nations, international organizations, and individuals have sought to bring order to an inherently disorderly phenomenon--potential and actual violent conflict among organized political entities. Specifically, War and Governance: International Security in a Changing World Order analyzes a number of critical issues such as whether regional security institutions have distinct advantages and liabilities in promoting international security, as compared with universal organizations like the United Nations. Other important questions are addressed, as well.